Collections, Walks, and Cultural Landscapes: Slovenian–Italian Cross-Border Heritage Initiatives - Ledinek Lozej, Špela; Pisk, Marjeta (Traditiones, 2021)
This article presents three examples of Slovenian–Italian cross-border heritage initiatives. The ZBORZBIRK project linked thirty-four collections from the border area. The Walk of Peace trail from the Alps to the Adriatic connects the most important remnants and monuments of the Isonzo Front in Slovenia and Italy. The municipalities in Brda/Collio are working to nominate the cultural landscape of this area for the UNESCO World Heritage List. The comparison presents the scope of the cross-border initiatives, the actors, their motivations, the actions taken, and their longevity—that is, the imprints in the cultural heritage discourse between the tourism industry and identity politics.